The Level of Knowledge about Toxoplasmosis among University Students in Rabat in Morocco. (26th July 2021) - Ait Hamou, Sanaa; Lamhamdi, Brahim; Hayah, Ichraq; Belbacha, Imane; Sadak, Abderrahim; Laboudi, Majda
Abstract : The aim of this descriptive cross-sectional study is to evaluate the knowledge of toxoplasmosis among medical, biology, and veterinary students in Rabat in Morocco. The data was collected by using a questionnaire which includes demographic characteristics, epidemiology, diagnosis, and clinical issues related to knowledge of toxoplasmosis. During analysis, the study groups were divided based upon their specialty of students who were medical, biology, and veterinary students. Out of 230 students, 55.2% were female and 44.8% were male. The average age of the study population is 21.7 ± 02 years. Less than half (42.6%) have heard of the disease; most of them have heard from faculty during studies in classrooms with 75.8%, and 3.2% were from the internet. Only 36.5% knew the correct causative agent of toxoplasmosis, and 32.1% were aware of the definitive host. The current study documented that there are gaps in the knowledge of the students regarding toxoplasmosis. Therefore, the present study puts the basis for future studies highlighting the importance of educating students to improve knowledge and attitudes towards toxoplasmosis.